Cardiovascular and hemodynamic parameters in women following prolonged CGRP inhibition using LBR-101, a monoclonal antibody against CGRP. (October 2014) - Bigal, Marcelo E; Walter, Sarah; Bronson, Michele; Alibhoy, Abbas; Escandon, Rafael
Background: The vascular effects of acute calcitonin gene-related peptide (CGRP) inhibition are well described, but the effects of sustained inhibition warrant further exploration in humans. Objectives: The objective of this article is to assess the effects of sustained CGRP inhibition on blood pressure, heart rate, and ECGs in healthy women ≥40 years of age. Methods: In this double-blind, placebo-controlled study, 31 women (mean age = 56) were randomized to receive placebo or an anti-CGRP monoclonal antibody at doses up to 2000 mg. Participants were confined for seven days and followed for 168 days. Cardiac telemetry was conducted for eight hours after infusion completion. Hemodynamic assessments and ECGs were conducted six times during Day 1 and periodically for three months. Results: No clinically relevant changes in systolic or diastolic blood pressure, heart rate, or ECG parameters (RR, PR, QRS, or QTcF) were observed when comparing baseline vs. post-dose time-points or in-between groups. No significant changes were seen for adjusted QTcF (baseline subtracted and placebo and baseline subtracted). No significant differences or relevant abnormalities were seen when comparing parameters obtained at Tmax vs. any other time-point. Conclusion: Sustained CGRP inhibition was not associated with hemodynamic or ECG changes in a population at an increased age risk for cardiovascular events.